Sistem Pendukung Keputusan Penentuan Lokasi Alat Pengamatan BMKG Di Provinsi Jambi - Margaretta S, Chinthya; Jasmir, Jasmir (Jurnal Manajemen Sistem Informasi, 2023)
Determining the remote site for each automatic equipment is one of the requirements for determining the location conditions in accordance with the operational conditions of weather equipment and seismic equipment. The Meteorology, Climatology and Geophysics Agency is a non-employee government agency that selects and determines a number of applicants who have qualified knowledge and skills and recruits new employees whose job is to provide information on meteorological, climatological and geophysica l activities. The system that can support the level of confidence in the location conditions according to the standards that must be achieved is using a decision support system for determining the location of BMKG observation tools, especially in Jambi Province. This system is designed using the mamdani fuzzy logic method where the AWS tool uses 6 (six) variables, namely location, location access, solar radiation potential, obstacles, communication networks, and security while the seismic tool uses 6 (six) variable, namely rock type, Tdom siteclass, location access, solar radiation potential, assessment results, and communication network. Mamdani fuzzy logic solves problems with intuitively approximated data with fuzzy logic controls. The results of the design of the decision support system prototype are in the form of survey locations shown on the map and the results of the decisions are in the form of feasible or infeasible conditions.